Analysis of the Code of Ethics of the Five Pandawa Character Perspective Accountants - Muhammad Aras Prabowo; Emilia Rachmi Muntaha; Habsyah Fitri Aryani (Innovation Business Management and Accounting Journal, 2025)
This study explores the use of "five" metaphors from the Mahabharata epic to describe five fundamental principles in accountant ethics. Each Pandavas character is associated with core principles that guide the professional behavior of accountants. This research method uses the literature method. The results of the discussion containing character and its history, Yudhishthira symbolizes integrity, emphasizing the importance of honesty and justice. Bhima reflects professional and caution competence, calling for strength in knowledge and skills. Arjuna describes objectivity, where accountants must maintain neutrality and not favor in decision making. Nakula is associated with the principle of confidentiality, emphasizing the importance of maintaining confidential information. Finally, Sahadeva symbolizes professional behavior, which requires accountants to act ethically and in accordance with professional standards. By using this analogy, this research offers a new way to understand and teach the principles of accountant ethics through the merging of cultural values ​​and professionalism.